Local structural features and composition of the Bi4Ge3O12:Dy3+ crystals: effect of doping concentration. Issue 34 (18th August 2020) - Kuz'micheva, Galina M.; Ivleva, Liudmila I.; Kaurova, Irina A.; Khramov, Evgeny V.; Dunaeva, Elizaveta E.; Svetogorov, Roman D.; Rybakov, Victor B.
Abstract : Dy 3+ -doped Bi4 Ge3 O12 crystals possess different actual compositions and structural behavior of Dy 3+ and Bi 3+ ions depending on the initial Dy2 O3 content. Abstract : Bismuth germanate Bi4 Ge3 O12 single crystals doped with 0.1 and 1.0 wt% Dy2 O3 have been successfully grown by the Czochralski method. The actual compositions of the Dy 3+ -doped Bi4 Ge3 O12 crystals have been refined for the first time using single-crystal and synchrotron powder X-ray diffraction. Different local structural behavior of the Dy 3+ and Bi 3+ ions in the Bi4 Ge3 O12 crystal matrix depending on the initial Dy 3+ content has been revealed by X-ray absorption spectroscopy. In the crystal with the refined composition (Bi3.996(11) Dy0.004 )Ge3 O12 (0.1 wt% Dy2 O3 ), the octahedron Dy 3+ O7 with a split vertex and vacancy octahedron Bi 3+ O5 are formed in adjacent octahedra. In the crystal with the refined composition (Bi3.952(47) Dy0.048 )Ge3 O12 (1.0 wt% Dy2 O3 ), the semi-octahedron Dy 3+ O5 and distorted octahedron Bi 3+ O6 are realized. A character of distribution of the residual electron density showed a probable decrease in the symmetry of Dy 3+ -doped Bi4 Ge3 O12 crystals that limits the possible maximum Dy 3+ content in the Bi4 Ge3 O12 crystal matrix. Noticeable fluctuations were not revealed in the absorption and luminescence spectra of Dy 3+ -doped Bi4 Ge3 O12 crystals.